Clara I. MARTÍNEZ CANTÓN y Sergio FERNÁNDEZ MARTÍNEZ (eds.).— Narradoras españolas de posguerra. Berna et al.: Peter Lang, 2022, 227 pp. - García Baumbach, Izan (Signa: Revista de la Asociación Española de Semiótica, 2023)
Reseña